2019
DOI: 10.1186/s13018-019-1218-6
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing lateral ankle instability by suture tape – a cadaver study

Abstract: Background Suture tape is a recent development to augment a Brostrom repair at least during the healing phase of the native tissues used for stabilization of the lateral ankle ligaments. The purpose of this study was to evaluate whether suture tape is an effective mechanical stabilizer against anterior talar drawer in a cadaver experiment when tested with a validated arthrometer. Methods Different stability conditions were created in 14 cadaveric foot and leg specimens.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…34 Thus, it was J o u r n a l P r e -p r o o f hypothesized that suture tape augmentation could improve ankle stability by increasing stability of the reconstructed ATFL and protecting the ligament. 15,16,17,18,19 A cadaveric study by Viens et al 6 was able to demonstrate that strength and stiffness of the suture tape augmented construct was not significantly different to the native ATFL.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 96%
See 1 more Smart Citation
“…34 Thus, it was J o u r n a l P r e -p r o o f hypothesized that suture tape augmentation could improve ankle stability by increasing stability of the reconstructed ATFL and protecting the ligament. 15,16,17,18,19 A cadaveric study by Viens et al 6 was able to demonstrate that strength and stiffness of the suture tape augmented construct was not significantly different to the native ATFL.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 96%
“…13,14 Suture tape augmentation or "internal bracing" is performed by using ultra high molecular weight polyethylene/polyester (UHMWPE) tapes and knotless bone anchors that are supposed to contribute to scar tissue formation by restoration of ankle stability and hence protect the repaired ligament during healing. 15,16,17,18,19 The aim of this study was to determine whether the use of suture tape augmentation would lead to improved clinical outcomes, increased stability, shorter postoperative immobilization J o u r n a l P r e -p r o o f and earlier return to activity and sports compared to Broström repair in surgical treatment of chronic lateral ankle instability (CLAI).…”
Section: Introductionmentioning
confidence: 99%
“…80 Two other cadaveric studies similarly found equal or better performance in the BR-ST group as measured by torque angle and total torque at failure. 71,83 Other biomechanical studies have noted the restoration of midfoot and hindfoot kinematics after BR-ST. 7, 50 Boey et al 7 used 3-D motion capture to measure range of motion (ROM) and average angle (AA) after rupture of sutureaugmented repair of ATFL, CFL, or both. All groups repaired with suture tape augmentation were able to at least partially restore foot and ankle kinematics, with the combined ATFL-CFL repair group achieving the best results.…”
Section: Technique Overviewmentioning
confidence: 99%
“…The results of MBG plasty with suture tape augmentation are superior to those of standard techniques (3,4,21,23) . Suture tape provides an increased mechanical stability to the ankle that helps prevent recurrence of injury to the lateral ligaments and underlying structures, improves functional stability, and optimizes active rehabilitation (21) .…”
mentioning
confidence: 91%